STATE-BUILDING IN AFGHANISTAN: DECENTRALIZATION VS. CENTRALIZATION - BOBOKULOV, Inomzhon (CENTRAL ASIA AND THE CAUCASUS, 2015)
It appears that the multinational and Mult confessional nature of Afghan society itself is the main reason prompting examination of the problem raised in this article. Recently, there has been increasingly lively discussion about whether Afghanistan will be able to choose a development model that could ensure Longterm peace and stability in the “heart of Asia.”